RARE LOSS-OF-FUNCTION MUTATIONS OF PTGIR IDENTIFIED IN FIBROMUSCULAR DYSPLASIA AND SPONTANEOUS CORONARY ARTERY DISSECTION. (April 2021) - Georges, Adrien; Albuisson, Juliette; Berrandou, Takiy; Dupré, Délia; Lorthioir, Aurélien; Amar, Laurence; Januszewicz, Andrzej; Motreff, Pascal; Adlam, David; Azizi, Michel; Gornik, Heather; Ganesh, Santhi; et al.
Abstract : Objective: Fibromuscular Dysplasia (FMD) and Spontaneous Coronary Artery Dissection (SCAD) are related, non-atherosclerotic arterial diseases mainly affecting middle-aged women. Little is known about their physiopathological mechanisms. We aimed to identify rare genetic causes to elucidate molecular mechanisms implicated in FMD and SCAD. Design and method: We analyzed 29 exomes that included familial and sporadic FMD. Follow-up was conducted by targeted or Sanger sequencing (1, 071 FMD and 365 SCAD patients) or lookups in exome (264 FMD) or genome sequences (488 SCAD), all independent and unrelated. We used TRAPD burden test to test for enrichment in patients compared to gnomAD controls. The biological effects of variants on receptor signaling and protein expression were characterized using transient overexpression in human cells. Results: We identified one rare loss-of-function variant (LoF) (MAFgnomAD = 0.000075) shared by two FMD sisters in the prostaglandin I2 receptor (hIP) gene (PTGIR), a key player in vascular remodeling. Follow-up in >1, 300 FMD patients revealed four additional LoF allele carriers and a putative enrichment in FMD (PTRAPD = 8 × 10-4), in addition to several rare missense variants. We confirmed the LoFs (Q163X and P17RfsX6) and one missense (L67P) to severely impair hIP function in vitro. Genetic analyses of PTGIR in SCAD revealed one patient who carries Q163X, one with L67P and one carrying a rare splicing mutation (c.768+1C>G), but not a significant enrichment (PTRAPD = 0.12) in SCAD. Conclusions: Our study shows that rare genetic mutations in PTGIR are enriched among FMD patients and found in SCAD patients, suggesting a role for prostacyclin signaling in non-atherosclerotic stenosis and dissection. Figure. No caption available.